If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 20 = 5x + -7 Reorder the terms: 20 + 2x = 5x + -7 Reorder the terms: 20 + 2x = -7 + 5x Solving 20 + 2x = -7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 20 + 2x + -5x = -7 + 5x + -5x Combine like terms: 2x + -5x = -3x 20 + -3x = -7 + 5x + -5x Combine like terms: 5x + -5x = 0 20 + -3x = -7 + 0 20 + -3x = -7 Add '-20' to each side of the equation. 20 + -20 + -3x = -7 + -20 Combine like terms: 20 + -20 = 0 0 + -3x = -7 + -20 -3x = -7 + -20 Combine like terms: -7 + -20 = -27 -3x = -27 Divide each side by '-3'. x = 9 Simplifying x = 9
| -5x-9y=-20 | | 3c+10=28 | | y=45xz+100xz+10z | | y=45xz+100+10z | | y=45xz | | 9-3(x+2)= | | 6x-8=16+4x | | -21x^2-33x+18= | | 270+16x=14x | | y+16=12 | | 4w^2-8wx-21x^2= | | 0.5cos(x)+0.08cos(2x-0.1)=0 | | 13x^2-27+28=0 | | 3m+23=8m-2 | | 4(w+1)+w=5(-1)+9 | | (h*f)(1)=4x-1-x+4 | | a^3y+1=0 | | x-2=7x+50 | | 8r+3=5r+12 | | -3(2x+4)=0 | | x=6-0.5y | | 7(11-8)=21 | | 7(p-8)=21 | | -7x=-49+98 | | 2x+2(2)=-10 | | 45+x=602 | | (3r-2s)(3r-2s)= | | 116-w=294 | | -8x-2(-1.5)=-13 | | -8(2)-2y=-13 | | 4a+(10-4a)=10 | | 5p-9=29+12 |